2014
DOI: 10.1002/gcc.22147
|View full text |Cite
|
Sign up to set email alerts
|

Frequent lack of GNAS mutations in colorectal adenocarcinoma associated with GNAS‐mutated villous adenoma

Abstract: Colorectal villous adenoma is thought to be associated with a high risk of progression to adenocarcinoma. To better characterize the genetic alterations involved in colorectal carcinogenesis related to villous adenoma, we analyzed mutations in APC, BRAF, KRAS, TP53, and GNAS in 12 colorectal adenocarcinomas associated with villous adenomas. APC, KRAS, and BRAF mutations were identified in five, 11, and one lesion, respectively, and most of these mutations were shared between the villous adenoma and the adenoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 18 publications
(31 reference statements)
5
18
0
Order By: Relevance
“…The recent study by Sekine et al might indicate that the mutation is relevant for tumor initiation but dispensable for malignant www.fhc.viamedica.pl tumor progression. It confirms our observation of the potential coincidence with a KRAS mutation [27]. Another recent study of 428 colon adenocarcinoma reported a rather low GNAS1 mutation rate of 2.3% and also a coincidence with KRAS mutations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The recent study by Sekine et al might indicate that the mutation is relevant for tumor initiation but dispensable for malignant www.fhc.viamedica.pl tumor progression. It confirms our observation of the potential coincidence with a KRAS mutation [27]. Another recent study of 428 colon adenocarcinoma reported a rather low GNAS1 mutation rate of 2.3% and also a coincidence with KRAS mutations.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, a very recent Japanese study of 12 villous adenomas in association with colon adenocarcinoma confirmed the high incidence since GNAS1 mutations were detected in 9 cases (75%). Interestingly, the GNAS1 mutations were shared in only 3 of the 12 adenocarcinomas (25%) of which 11 also harbored KRAS mutations [27]. It should be mentioned, however, that this study came from the same group that initially reported GNAS1 mutation in villous adenoma.…”
Section: Discussionmentioning
confidence: 76%
“…Mucinous colon/appendix cancers display phenotypic and genotypic characteristics that are predictive of responses to dual MEK‐PI3K inhibition. Mucinous colon cancers are more likely to occur in younger female patients; particularly the right colon; follow the serrated pathway for carcinogenesis; and are more likely to have RAS, RAF, and GNAS mutations . Similarly, mucinous appendix cancers are almost always KRAS mutant, and low‐grade histology almost uniformly demonstrates GNAS mutations .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we tested the efficacy of dual MEK‐PI3K drug therapy against mucinous colon/appendix cancers since these tumors demonstrate unique phenotypic and genotypic features that are likely to be predictive of sensitivity to this combination therapy. Genotypically, these tumors frequently demonstrate KRAS mutations, resulting in downstream activation of MAPK and PI3K signaling pathways . Phenotypically, mucinous tumors demonstrate high basal endoplasmic reticulum stress (ERS), and associated signaling pathways known as the upregulated protein response (UPR), likely due to high mucin 2 (MUC2) protein turnover .…”
Section: Introductionmentioning
confidence: 99%
“…These associated genes were a component of the associated gene network in adenocarcinoma. Finally, the last component of the associated gene network in adenocarcinoma was identified using the relevant literature (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). The four aforementioned components were then summarized as the associated gene network in adenocarcinoma.…”
Section: Materials Collection and Data Processingmentioning
confidence: 99%